Strategi Pemasaran Digital Scarlett dalam Membangun Loyalitas Konsumen Generasi Z di Industri Skincare Lokal - Septiyanti, Nur Dhea; Lira, Rahmadina; Zyfa, Evrillita; Chairunnisa, Kusuma (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The development of social media has driven significant changes in the marketing strategy of the beauty industry, especially in reaching Generation Z as a key market segment. Generation Z is known as a digital consumer who is very active on social media and tends to rely on visual content, influencer recommendations, and public figures in determining skincare product purchasing decisions. This study aims to analyze the role of digital marketing strategies in making Scarlett Whitening one of the skincare brands that is in demand by Generation Z. The research method used is a Systematic Literature Review (SLR) by reviewing various national journal articles relevant to the topics of digital marketing, social media, brand ambassadors, and consumer behavior of Generation Z. The results of the study show that social media, especially Instagram, plays an important role in increasing brand awareness and consumer purchasing interest towards Generation Z. Inaddition, brand ambassadors are proven to be a dominant factor in shaping trust and consumers of the Scarlett brand. The research findings also show that Generation Z is more responsive to marketing strategies that are authentic, interactive, and relevant to their lifestyle. Thus, the combination of optimal social media utilization and the appropriate use of brand ambassadors is key to Scarlett's success in attracting Generation Z. This research is expected to provide theoretical contributions to digital marketing studies and serve as a practical reference for skincare industry practitioners in designing effective marketing strategies for Generation Z.